Three Dimensional Carotid and Femoral Ultrasound is not Superior to Two Dimensional Ultrasound as a Predictor of Coronary Atherosclerosis Among Men With Intermediate Cardiovascular Risk. (January 2020) - Jarauta, Estíbaliz; Laclaustra, Martin; Villa-Pobo, Rosa; Langarita, Raquel; Marco-Benedi, Victoria; Bea, Ana M.; León-Latre, Montse; Casasnovas, Jose A.; Civeira, Fernando
Abstract : Background: Current cardiovascular disease (CVD) risk stratification scales, drawn up from traditional risk factors, have important limitations. The detection of subclinical atherosclerosis, by a non-invasive technique such as peripheral arteries ultrasound (US) may improve cardiovascular risk (CVR) stratification, especially in intermediate risk population. Our aim was to compare the predictive power of atherosclerotic plaques detected in carotid and femoral arteries by 2-dimensional (2D) vs. 3-dimensional (3D) US for positive coronary artery calcium score (CACS), used as a proxy for CVD, in a middle-aged sample with intermediate 10-year CVR (7.5–20%). Methods: To detect atherosclerotic plaques by 2D vs. 3D US scan of carotid and femoral arteries and comparison of their association with CACS obtained by computed tomography (CT) of subjects with intermediate CVR belonging to the Aragon Workers' Health Study. Results: 120 men were included, with a 10.4% average 10 years CVR. Forty-one (34.2%) participants had CACS ≥ 1. 90 participants (75%) had at least one plaque detected by 2D scan while 85 participants (70.8%) had at least a plaque detected by 3D US. Conventional CVR estimates c-statistic for CACS was .590. Although the variables most predicted of CACS ≥ 1 were those measured by 3D US (total plaque volume and mean of plaque density, c-statistics: .743 and .750 respectively), their predictive capacity was not statistically significantly different from the number of territories with plaque, measured either by 2D and 3D US (c-statistics .728 to .740 respectively). Conclusion: Subclinical atherosclerosis measured by 2D and 3D US were better predictors of CACS ≥ 1 than CVR estimated by conventional guidelines. In our sample, 3D US did not show any significant advantages with respect to 2D US for the prediction of coronary atherosclerosis.